1982
DOI: 10.1083/jcb.95.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules and protein secretion in rat lacrimal glands: localization of short-term effects of colchicine on the secretory process.

Abstract: ABSlRACl The pathway and kinetics of the secretory protein transport in rat lacrimal exorbital gland have been established by an in vitro time-course radioautographic study of pulse-labeled protein secretion.The colchicine-sensitive steps have been localized by using the drug at various times with respect to the pulse labeling of proteins. Colchicine (10/IM) does not block any step of the secretory protein transport, but when introduced before the pulse it decreases the transfer of labeled proteins from the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Alternatively, Golgi membrane enroute to peripheral sites could move through existing membrane structures, like the ER (Saraste and Svensson, 1991;Saraste and Kuismanen, 1992), which extend peripherally throughout the cytoplasm even during nocodazole treatment (Terasaki, 1986). Both of these models are consistent with previous observations on Golgi fragmentation after microtubule disruption, which found that fragmentation is sensitive to energy depletion and membrane traffic perturbants (Turner and Tartakoff, 1991; Table 1), and that rudimentary Golgi formations appear at peripheral sites before central Golgi structures are affected (Busson-Mabillot et al, 1982;Pavelka and Ellinger, 1983). Our observations that ERGIC-53 moves through the ER before accumulating in peripheral fragments during nocodazole treatment ( Figure 3), and that Golgi reassembly at peripheral ER sites during nocodazole treatment occurs whether Golgi enzymes are redistributed from centrosomal stacks or from the ER (during BFA washout), however, favor the latter of these models.…”
Section: Discussionsupporting
confidence: 80%
“…Alternatively, Golgi membrane enroute to peripheral sites could move through existing membrane structures, like the ER (Saraste and Svensson, 1991;Saraste and Kuismanen, 1992), which extend peripherally throughout the cytoplasm even during nocodazole treatment (Terasaki, 1986). Both of these models are consistent with previous observations on Golgi fragmentation after microtubule disruption, which found that fragmentation is sensitive to energy depletion and membrane traffic perturbants (Turner and Tartakoff, 1991; Table 1), and that rudimentary Golgi formations appear at peripheral sites before central Golgi structures are affected (Busson-Mabillot et al, 1982;Pavelka and Ellinger, 1983). Our observations that ERGIC-53 moves through the ER before accumulating in peripheral fragments during nocodazole treatment ( Figure 3), and that Golgi reassembly at peripheral ER sites during nocodazole treatment occurs whether Golgi enzymes are redistributed from centrosomal stacks or from the ER (during BFA washout), however, favor the latter of these models.…”
Section: Discussionsupporting
confidence: 80%
“…Cell functions affected at molecular level are enzyme activities (Volpe 1979, Wilfred 1977, Ewart 1982, Chen et al 1976, Nicklas et al 1973, redistribution of enzymes and proteins (Borensztajn et al 1975, Brimijoin 1974, Parish and Pelli 1974, Ray mackers and Hugon 1973, Thyberg et al 1980, Kreutzberg 1969, Sjostrand et al 1970, James et al 1970, permeability of cells (Berlin 1973, Mizel and Wilson 1972, Cheng and Katsoyannis 1975, Tauber and Reutter 1980, distribution of receptors on membrane (Whittaker et al 1981b), release of secretory products (Busson-Mabillot et al 1982, Jansen and Bornstein 1974, Gordon and Werb 1976, Ehrlich et al 1974, Reaven and Reaven 1980, and DNA and protein synthesis (Piatigorsky et al 1972, Daniels 1972, Redman et al 1978, Friedkin and Rozengurt 1980. Movement or shape changes of cells, division, phagocytosis, endocytosis, and translocations of organelles are examples of cell events affected at supramolecular level (Mori et al 1982, Bhisey and Freed 1971, Malawista 1975.…”
Section: Resultsmentioning
confidence: 99%
“…With the use of various microtubule-perturbing drugs, the role of microtubules in protein transport has been extensively studied in different cell systems (Busson-Mabillot et al, 1982;Achler et al, 1989;Stults et al, 1989). Nocodazole, a depolymerizing drug (De Brabander et al, 1976), and taxol, a hyperpolymerizing drug (De Brabander et al, 1981;Horwitz et al, 1986), have been used to examine the role of the microtubular cytoskeleton in sorting in MDCK cells.…”
Section: Introductionmentioning
confidence: 98%